Excited State Absorption in Tb Activated Phosphor Powders - Raue, R.; Young, D. A.; dos Santos, L. M.; Verhaar, H. C. G.; Monteiro, T.; Albin, S.; von Seggern, H.; Giakoumakis, G. E.; Chapoulie, R.; Mishra, K. C.; Grün, M.; Uhrig, A.; et al. (Springer US, 1991)
Optimal transitions between the 5D4 excited state of the Tb3+ (4f)8 configuration and the crystal field splitted components of the (4f)85d configuration have been observed using high-resolution laser excitation of Tb-doped powder samples. The Excited State Absorption (ESA) spectra of Tb3+ in YAG and YAGaG show broad excitation bands due to these transitions and superimposed relatively narrow lines due to transitions within the (4f)8 configuration.